2021
DOI: 10.1177/00219983211031637
|View full text |Cite
|
Sign up to set email alerts
|

The micro/macro mechanical approach of reinforced braid composite used in tribology

Abstract: Self-lubricant composite is a flourish scope of technology that merits academic and industry attention, as it is a specific part which essentially employed in acute operation conditions. In the present study, the mechanical properties of the self-lubricating composite of two-dimensional (2D) and three-dimensional (3D) braid were investigated. The composites contained Polytetrafluoroethylene (PTFE) fibers as a lubricant and glass, carbon, and Kevlar as a reinforcement, hierarchically incorporated into the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For the PTFE material, it exhibits excellent linear and isotropic material properties, with consistent mechanical strength, thermal stability, and electrical insulation ability. According to the work of Zahabi et al [21] and Bao et al [22], the elastic modulus of PTFE material is statistically considered to be an increasing function of hardness, and it can be obtained by indentation technique or the Oliver-Pharr method.…”
Section: Mechanical Property Characterization Of Seal Materialsmentioning
confidence: 99%
“…For the PTFE material, it exhibits excellent linear and isotropic material properties, with consistent mechanical strength, thermal stability, and electrical insulation ability. According to the work of Zahabi et al [21] and Bao et al [22], the elastic modulus of PTFE material is statistically considered to be an increasing function of hardness, and it can be obtained by indentation technique or the Oliver-Pharr method.…”
Section: Mechanical Property Characterization Of Seal Materialsmentioning
confidence: 99%
“…Although, the poor interfacial shear strength (IFSS) value of PTFE has suppressed their potential for use in various applications. 4,12 Despite enormous studies performed on multiple methods for embedding solid lubricant in composites, too little attention has been paid to use hierarchical braid structure. Wang and Yan, 13 Bahadur et al, 14 and Yang 15 indicated that PTFE composite wear life is brief because it cannot shape durable tribofilms.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption of stresses generated during wear at the friction composite interface is mainly done by fibers. [3][4][5] Thanks to its intrinsic self-lubrication, high modulus/strength, and good thermal stability, carbon fiber can be used in various composites. 6 However, some works have yielded contradictory findings concerning the influence of carbon fiber on tribological behavior, indicating poor frictional properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the tribological properties, mechanical characteristics of the composite must be analyzed [25]. One of the tests to examine the strength of bearings is the compressive strength test because the bearings are affected by radial loads [26].…”
Section: Introductionmentioning
confidence: 99%